The relationship between motor ability and change-of-direction kinematics in elite college basketball players - Sasabe, K.; Sekine, Y.; Hirose, N. (International Journal of Sport & Health Science, 2022)
The change-of-direction speed is an essential physical component in basketball. This study aimed to reveal the relationship between change-of-direction kinematics and the related motor abilities in basketball players. Motor abilities, including squat, sprint speed, vertical jump, and horizontal jump, were measured in 14 male collegiate basketball players. Furthermore, the change-of-direction speed and kinematics during the change-of-direction task, including the trunk lean angle and center-of-gravity height, were evaluated. Correlations between change-of-direction time and kinematics were assessed using the Pearson product-moment correlation coefficient. Once significant correlations were detected, correlations between motor abilities and change-of-direction kinematics variables related to change-of-direction time were assessed using the Pearson product-moment correlation coefficient. There were significant correlations between change-of-direction time and center-of-gravity height (r=0.54), and trunk lean angle (r=-0.74). Moreover, there was a strong correlation (r=-0.53) between the center-of-gravity height and lower body strength. Improving lower muscle strength and change-of-direction kinematics may be necessary to enhance the overall change-of-direction performance.